Technical-Tactical Actions of Young Wrestlers at the Stage of Primary Training Analysis (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
In this article, the analysis of the technical and tactical actions of young wrestlers at the initial training stage is considered.We know that the development of technical and tactical wrestling sports is in the first place. Correct use of pedagogical teaching methods during training is the most effective way to thoroughly develop technique.